Trade and Manufacturing Jobs in Germany - Dauth, Wolfgang; Findeisen, Sebastian; Suedekum, Jens (American Economic Review, 2017)
The German economy exhibits rising service and declining manufacturing employment, but this decline is much sharper in import-competing than export-oriented branches. We first document the individual-level job transitions behind those trends. They are not driven by manufacturing workers who smoothly switch to services. The observed shifts are entirely due to young entrants and returnees from non-employment. We then investigate if rising trade with China and Eastern Europe causally affected those labor flows. Exploiting variation across industries and regions, we find that globalization did not speed up the manufacturing decline in Germany. It even retained those jobs in the economy.